Interaksi Simbolik: Suatu Pengantar - Dadi Ahmadi (MediaTor (Jurnal Komunikasi), 2008)
Symbolic interaction focuses on ‘interpretation’ over subjective meaning derived from interaction of people with the others of his/her environment. As stated clearly in its name, symbolic interaction emphasized a close relationship an exchange between symbol and interaction. These exchanges produced special meanings and interpretations, unique for each person involved. Symbolic is derived from the word ‘symbol’ which means signs resulted from consensus. Symbolic Interaction tried to ‘entering’ meaning process and subject defining by employing participant observation to watch carefully how subject define themselves and their actions respectfully, based on definitions and meanings given by others in their environment.